2021
DOI: 10.1186/s12917-021-02869-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Arthrospira platensis improves systemic antioxidant potential and changes plasma lipids without affecting related hepatic metabolic pathways in post-weaned piglets

Abstract: Background The ability of a high level of dietary Arthrospira platensis, individually or in combination with two exogenous carbohydrate-degrading enzymes (lysozyme and Rovabio®), to improve systemic antioxidant potential and hepatic lipid metabolism was tested in piglets. Forty male post-weaned piglets, sons of Large White × Landrace sows crossed with Pietrain boars, were allocated into 4 groups (n = 10) and fed during 28 days one of the following diets: 1) a control basal diet (cereal and soyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…For Chlorella vulgaris , the most important finding was the hepatic deposition of n -3 PUFA, in particular eicosapentaenoic acid (EPA), and the subsequent beneficial reduction of n -6/ n -3 ratio 20 . In turn, dietary Arthrospira platensis increased systemic lipids, namely total cholesterol and LDL-cholesterol in weaned piglets, while boosting the antioxidant potential 19 . In view of these findings, we hypothesized that similar or additional beneficial effects could be obtained with the seaweed U. lactuca .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…For Chlorella vulgaris , the most important finding was the hepatic deposition of n -3 PUFA, in particular eicosapentaenoic acid (EPA), and the subsequent beneficial reduction of n -6/ n -3 ratio 20 . In turn, dietary Arthrospira platensis increased systemic lipids, namely total cholesterol and LDL-cholesterol in weaned piglets, while boosting the antioxidant potential 19 . In view of these findings, we hypothesized that similar or additional beneficial effects could be obtained with the seaweed U. lactuca .…”
Section: Introductionmentioning
confidence: 95%
“…Our research team has previously reported the effects of dietary microalgae with or without CAZyme supplementation on blood metabolites and hepatic lipids of weaned piglets 18 , 19 and growing-finishing pigs 20 . For Chlorella vulgaris , the most important finding was the hepatic deposition of n -3 PUFA, in particular eicosapentaenoic acid (EPA), and the subsequent beneficial reduction of n -6/ n -3 ratio 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Serum biochemical profile analysis has been previously described by Madeira et al 15 . Triacylglycerols (TAG), total cholesterol, phospholipids, urea, total protein, LDL-cholesterol, HDL-cholesterol, glucose and creatinine concentrations and serum hepatic markers were determined in a Modular Hitachi Analytical System (Roche Diagnostics, Mannheim, Germany) using diagnostic kits (Roche Diagnostics, Meylan, France) following manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…In turn, it also increased the accumulation of n-3 PUFA (including eicosapentaenoic acid, EPA) and reduced hepatic n-6/n-3 ratio 14 . On the other hand, dietary A. platensis increased serum total lipids, total cholesterol and LDL-cholesterol of weaned piglets, whilst improving antioxidant potential 15 . Even though L. digitata has a very different composition, analogous or additional effects can also be found.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation